A study of some airflow resistivity models for multi-component polyester fiber assembly. (October 2018) - Yang, Tao; Mishra, Rajesh; Horoshenkov, Kirill V.; Hurrell, Alistair; Saati, Ferina; Xiong, Xiaoman
Abstract: The airflow resistivity is a key parameter to predict accurately the acoustical properties of fibrous media. There is a large number of theoretical and empirical models which can be used to predict the airflow resistivity of this type of porous media. However, there is a lack of experimental data on the accuracy of these models in the case of multi-component fibrous media. This paper presents a detailed analysis of the accuracy of several existing models to predict airflow resistivity which make use of the porosity, bulk density and mean fibre diameter information. Three types of polyester (PET) materials made using regular PET, hollow PET and bi-component PET with a range of densities are chosen for this study. It is shown that some existing models largely under- or overestimate the airflow resistivity when compared with the measured values. A novel feature of this work is that it studies the relative performance of airflow resistivity prediction models that are based on the capillary channel theory and drag force theory. These two groups of models are then compared to some purely empirical models. It is found that the prediction error by some models is unacceptably high (e.g. >20–30%). The results suggest that there are existing models which can predict the airflow resistivity of multi-component fibrous media with 8–10% accuracy.